The Insidious Momentum of American Mass Incarceration - Zimring, Franklin E. (Oxford University Press USA - OSO, 2020)
In The Insidious Momentum of American Mass Incarceration provides a comprehensive understanding of when, how, and why the United States became the world leader in incarceration to further propose a range of strategies that can reduce prison population and promote rational policies of criminal punishment. Zimring argues that the most powerful enemy to reducing excess incarceration are simply the mundane features of state and local government, such as elections of prosecutors and state support for prison budgets.